POLA KALIMAT PADA KUMPULAN DONGENG GADIS KOREK API KARYA H.C. ANDERSEN (SUATU KAJIAN SINTAKSIS) - Veria Septianingtias, author (JURNAL PESONA, 2015)
This study described syntactic structure on fairy-tale collection of Gadis Korek Api by H.C. Andersen. The study which seen from syntactic structure is sentence pattern based on function category, category, and syntactic role. This study aimed to describe syntactic structure on fairy-tale collection of Gadis Korek Api by H.C. Andersen and itâs distribution towardh Indonesian language. This research used qualitative method and note method was employed for collecting the data. In analysing the data, the researcher used Agih method by applying Immediate Constituent Analysis technique (ICA) as a basic technique. A book entitled Gadis Korek Api and others fairy-tale are the work of danish author, H.C. Andersen that used Indonesian standard. The analysis showed syntactic structure of fairy-tale language which form of sentence pattern based on the user, the pattern of imperative sentence, sentence pattern contains conjunction, and sentence pattern of complex sentences. Keywords: Sentence Pattern; Fairy-tale; Syntactic.